2016
DOI: 10.18632/oncotarget.12202
|View full text |Cite
|
Sign up to set email alerts
|

Associations of P16INK4a promoter hypermethylation with squamous intra-epithelial lesion, cervical cancer and their clinicopathological features: a meta-analysis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…It has been found that during the development of carcinomas, including various stages of cervical cancer, numerous epigenetic changes, such as hyperand hypomethylation of DNA and tumor suppressor genes and modification of histones associated with the promoter regions of regulatory genes are observed. The results of meta-analysis confirm the hypermethylation of p16INK4a as an epigenetic marker for the progression of carcinogenesis in cervical cancer [65]. Expression of tumor suppressor genes, oncogenes, and growth factors is regulated by many histone-modifying enzymes, such as deacetylases and histone acetyltransferases; changes in the expression of histone modifiers also lead to epigenetic control of gene expression [16].…”
Section: Mechanisms Of Cervical Carcinogenesismentioning
confidence: 67%
See 2 more Smart Citations
“…It has been found that during the development of carcinomas, including various stages of cervical cancer, numerous epigenetic changes, such as hyperand hypomethylation of DNA and tumor suppressor genes and modification of histones associated with the promoter regions of regulatory genes are observed. The results of meta-analysis confirm the hypermethylation of p16INK4a as an epigenetic marker for the progression of carcinogenesis in cervical cancer [65]. Expression of tumor suppressor genes, oncogenes, and growth factors is regulated by many histone-modifying enzymes, such as deacetylases and histone acetyltransferases; changes in the expression of histone modifiers also lead to epigenetic control of gene expression [16].…”
Section: Mechanisms Of Cervical Carcinogenesismentioning
confidence: 67%
“…According to different research, in HPV infection and cervical cancer there are various epigenetic changes and DNA methylation processes, and the participation of microRNAs in these processes has been described [18,19,65,83,[85][86][87][88]. At present, many of these processes have been studied insufficiently, and their interpretation is ambiguous, so the molecular mechanisms underlying these pathological changes are being investigated [11,14,85].…”
Section: Mechanisms Of Cervical Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter regions of p16 are often methylated, which decreases the levels of p16 in cervical cancer (8). Previous studies have demonstrated that p16 promoter methylation is closely associated with the development and progression of cervical cancer, so it is considered a potential diagnostic and therapeutic target (9,10). The changes involved in DNA methylation are controlled by DNA methyltransferases (DNMTs) (11).…”
Section: Introductionmentioning
confidence: 99%
“…The imprint and non-imprint methylation marks at these DMRs are established during gametogenesis and affected by environmental exposures (Li et al, 2016). P16 methylation is strongly associated with smoking in different pathological conditions, including lung cancer and cervical cancer (Han et al, 2016; Han et al, 2017; Wang et al, 2017). However, the relationship between these genes, tobacco/alcohol exposure, and male infertility has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%